Social cohesion among Syrian and Turkish children, adolescents, and young adults in Turkey - Nitya Mittal; Marta Parigi; Sebastian Vollmer (International Migration, 2024)
Turkey has received a large influx of Syrian refugees since the start of Syrian civil war in 2011. Integration and social cohesion have become important issues for public policy in Turkey. We study social cohesion among young Turkish nationals and Syrian refugees. Our study sample comprises of adolescents and young adults (12–300.167emyears), and children (6–110.167emyears) who participated in events of the “Education Program for Syrian Refugees and Host Communities” (BILSY) program conducted by the German Corporation for International Cooperation (GIZ). Social cohesion among adolescents and young adults is measured along three dimensions: sense of belonging, trust, and relational capacity. For children, we use behavioural games to measure two dimensions of social cohesion – altruism and trust. Our results show high social cohesion for both age groups, though lack of trust among Turkish nationals towards Syrian nationals is an area of concern. We also evaluate the impact of participation in BILSY program events using a randomised design and find that it had no impact on social cohesion. Our article adds to the limited literature on social cohesion among children and youths in countries affected by forced displacement.
Keywords: 300